ANALISIS TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN KEUANGAN DESA - Pratiwi, Lidia; Nuraisyiah, Nuraisyiah; S, Masnawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This research aims to analyze the transparency and accountability of village financial management in Ajakkang village, Soppeng Riaja sub-district, Barru district. The variables of this research are transparency and accountability in village financial management which are analyzed using indicators that have been adapted in Minister of Home Affairs regulation number 20 of 2018 concerning village financial management. Respondents in this study were the village head, village secretary, village treasurer, BPD chairman and village community. Data collection was carried out using interview and documentation techniques. The data analysis used is qualitative descriptive data analysis. The results of this research indicate that the principle of transparency in village finances management in Ajakkang village, Soppeng Riaja subdistrict, Barru district at the reporting stage was not fully achieved because there were indicators that were not realized so that it was quite in accourdance with Minister of Home Affairs regulation number 20 of 2018. Meanwhile, the principle of accountability in Ajakkang village, Soppeng Riaja sub-district, Barru district, it is also quite appropriate at the planning, implementation, administration and accountability stages in Home Affairs Regulation Number 20 of 2018.